Efficacy and risk of mRNA vaccination in patients with autoimmune inflammatory rheumatic diseases - Yasuhiro Kato; Takayoshi Morita; Atsushi Kumanogoh (BMC, 2023)
Abstract Coronavirus disease 2019 (COVID-19), which spread worldwide from Wuhan, China, in 2019, appeared for a time to be overcome by the remarkable efficacy of mRNA vaccines; however, new variants of severe acute respiratory syndrome coronavirus 2 have emerged and remain rampant. The involvement of the virus in the emergence of variant strains and the relationship between vaccine efficacy and immunosuppressive drugs have attracted significant attention, particularly with regard to patients with autoimmune inflammatory rheumatic disease (AIRD) who take immunosuppressive drugs. This review outlines the relationship between mRNA vaccines, one of the key strategies against COVID-19, and AIRD and discusses the immune response elicited by mRNA vaccines. Furthermore, the impact of immunosuppressive agents on the mRNA vaccine-induced immune response in patients with AIRD and side effects of the vaccine, such as exacerbation of the underlying disease, is outlined.